The Decision Support System for Product Purchasing - Kafin, Kafin; Galinium, Maulahikmah; Erwin, Alva (Swiss German University, 2015)
In the development of the technology, the variety of notebook has become diverse. It can be differed by its rice, model, type, and functionality, such as weight, screen size, processor, hard disk, memory (RAM), and graphic card. All of that diversity has become the consideration by the one who looking for a notebook. There has a problem where the buyer is so confused in deciding which notebook that is suitable with their needs. Decision support system is considered as one of the solutions to handle that kind of problem. Fuzzy Tahani Algorithm that uses the relative and qualitative natural language as the user input criteria is believed to be able to help the notebook buyer in making the decision. The result is shown that the decision support system for purchasing multi criteria product such as notebook, based on the user input criteria with the Fuzzy Tahani algorithm, is able to help the user to get the alternative product that can be recommended to them.